Visible Light Irradiation-Mediated Drug Elution Activity of Nitrogen-Doped TiO2 Nanotubes. (10th January 2013) - Oh, Seunghan; Moon, Kyung-Suk; Moon, Joo-Hee; Bae, Ji-Myung; Jin, Sungho
Abstract : We have developed nitrogen-doped TiO 2 nanotubes showing photocatalytic activity in the visible light region and have investigated the triggered release of antibiotics from these nanotubes in response to remote visible light irradiation. Scanning electron microscopy (SEM) observations indicated that the structure of TiO 2 nanotubes was not destroyed on the conditions of 0.05 and 0.1 M diethanolamine treatment. The results of X-ray photoelectron spectroscopy (XPS) confirmed that nitrogen, in the forms of nitrite (NO 2 - ) and nitrogen monoxide (NO), had been incorporated into the TiO 2 nanotube surface. A drug-release test revealed that the antibiotic-loaded TiO 2 nanotubes showed sustained and prolonged drug elution with the help of polylactic acid. Visible light irradiation tests showed that the antibiotic release from nitrogen-doped TiO 2 nanotubes was significantly higher than that from pure TiO 2 nanotubes (P < 0.05 ).